Current aspects of comprehensive treatmentfor advanced breast cancer (literature review and analysis of original material) - D. D. Pak; L. V. Bolotina; A. S. Suhotko (Сибирский онкологический журнал, 2016)
The review is devoted to the treatment methods for advanced breast cancer. The analysis of international studies aimed to assess the efficacy of surgical treatment for stage IV breast cancer patients was carried out. The role of the current drug therapy as a factor contributing to increase in the overall survival was studied